Transbronchial Lung Biopsy, Nodular Opacities, Interstitial Lung Disease - Simon, Mărioara; Pop, Monica; Vremăroiu, Petruţ; Vallasek, Kinga Aletta (Medicine and Pharmacy Reports, 2014)
Transbronchial lung biopsy (TBLB) is a bronchoscopy associated technique, a viable option to open lung biopsy in patients with interstitial lung disease or nodular masses situated outside the direct endoscopic view. We aimed to evaluate the diag- nostic efficacy and complications of transbronchial lung biopsies performed in the Endoscopy Department of the Pneumology Hospital of Cluj-Napoca, between 2007 - 2011 and present some representative cases of diagnostic value. Out of 194 analyzed cases which performed TBLB, we had valid pulmonary tissue samples in 174 cases, with confirmation rate of 61.94% and 1,03% complications rate.